Cu/TiO2 nanoparticles modified nitrogen-doped graphene as a highly efficient catalyst for the selective electroreduction of CO2 to different alcohols. (March 2018) - Yuan, Jing; Yang, Man-Ping; Hu, Qiao-Li; Li, Shi-Ming; Wang, Huan; Lu, Jia-Xing
Graphical abstract: Highlights: Cu/TiO2 nanoparticles anchored onto N-doped graphene (Cu/TiO2 /NG) are prepared by a facile strategy for the first time. The resulting solid powder catalyst exhibits high active, selective and stable for electroreduction CO2 . Cu/TiO2 /NG nanocomposite has dual catalytic activity for the electrochemical reduction of CO2 . Abstract: The construction of an efficient and robust catalyst for the electrochemical reduction of carbon dioxide into energy-rich products has recently received considerable attention. Herein, a Cu/TiO2 nanoparticles modified nitrogen-doped graphene (Cu/TiO2 /NG) carbon material is fabricated for the selective reduction of CO2 into different alcohols. We found the Cu/TiO2 /NG nanocomposite across a range of potentials for the electroreduction of CO2 exhibits dual catalytic ability, possessing an outstanding ability to produce methanol (reaching a maximum faradaic efficiency of 19.5% at a potential of −0.20 V vs. the reversible hydrogen electrode (RHE)) and a capability to produce ethanol (with a high faradaic efficiency up to 43.6% at −0.75 V vs. RHE). In addition, the Cu/TiO2 /NG composite shows remarkable stability and reusability at both reductive potentials in the electrochemical process. The designed Cu/TiO2 /NG composite may offer a new simple method based on earth-abundant metals to construct robust electrocatalysts for CO2 reduction.